THE ECONOMIC EFFECTS OF THE ESTABLISHMENT OF THE GREAT PORT OF FAW AND ITS LINK TO THE BELT AND ROAD INITIATIVE - Amjed Radha Hasan Al-Zahidee; Dr. Hamdiya Shaker Muslim Al- Edam (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Iraq has a single sea port on the Arabian Gulf, on which four commercial ports and two oil ports have been established. Despite the small Iraqi coastline on the Gulf, which does not exceed 60 km, which is the smallest area among the Gulf countries, this small area represents the maritime port of Iraq on the high seas. If it is properly utilized, it will have great returns on the economy. Iraq has an important strategic position in shortening the distances between East and West. And if Iraq wants to catch up with global developments, especially in the field of maritime transport and the establishment of modern and advanced ports, it must expedite the establishment of the great port of Faw, as Iraq’s possession of important commercial ports, but these ports do not meet Iraq’s growing needs, as they are internal ports with limited depths and do not directly overlook The Arabian Gulf, as well as in the event that Iraq is linked to the Belt and Road Initiative and is ready to exercise its vital role in linking the Asian East and the European West, from the ports of the Arabian Gulf to the ports of the Mediterranean. This necessitates accelerating the completion of the Faw port project due to its importance in transporting trade and considering it the gateway that moves the wheel of economic development and the great economic benefits it will bring to it through the establishment of the dry canal, which shortens the time and cost in transporting global trade.